Latent profile and influencing factors of volume management behaviors in patients with chronic heart failure: a cross-sectional study - Chen, Lu; Wu, Rui; Wang, Huiwen; Li, Yinjie; Liu, Mengdie; Chen, Hua; Xiao, Dan; Xiong, Xiaoyun (Frontiers in Cardiovascular Medicine, 2025)
AimsThis study aimed to identify latent profiles of volume management behaviors among patients with chronic heart failure using latent profile analysis and to explore the factors influencing different behavioral profiles.MethodsA total of 381 patients with chronic heart failure were recruited through convenience sampling from the department of cardiovascular medicine at a tertiary hospital in Nanchang City, between December 2024 and May 2025. Data were collected using the General Information Questionnaire, the Home Volume Management Self-Rating Scale for Patients with Chronic Heart Failure, the Self-Efficacy for Managing Chronic Disease 6-Item Scale, and the Social Support Rating Scale. Latent profile analysis was conducted on the volume management behaviors of patients with chronic heart failure, and multinomial logistic regression analysis was used to examine the factors influencing the different latent profiles.ResultsThree distinct latent profiles of volume management behavior were identified: “low capacity-vulnerable type” (39.9%), “high capacity-robust type” (15.5%), and “moderate capacity-dependent type” (44.6%). Multivariate logistic regression analysis revealed that educational level, duration of disease, social support, and self-efficacy were factors influencing the latent profiles of volume management behaviors in chronic heart failure.ConclusionOverall, volume management behaviors in patients with chronic heart failure were suboptimal, with notable variation across different profiles. Tailored interventions based on these profile characteristics and influencing factors may enhance volume management abilities in this population.